Effectiveness and Challenges of Canva-Based Online Collaborative Learning in Interactive Multimedia Projects Development - Sella Mawarni; Hartoto Hartoto (CV. Media Inti Teknologi, 2026)
Background: Online Collaborative Learning (OCL) has become increasingly relevant in higher education, particularly in project-based courses that require the development of digital products. Canva, as a cloud-based design platform, provides real-time collaboration features that may support collaborative knowledge construction; however, empirical evidence regarding its implementation within a structured OCL framework remains limited.Aims: This study aims to analyze the effectiveness and challenges of implementing Canva-based Online Collaborative Learning in interactive multimedia project development. Methods: A quantitative survey design was employed involving 85 undergraduate students from the Primary School Teacher Education and Educational Technology programs at the State University of Makassar. Data were collected using a validated 10-item Likert-scale questionnaire with high reliability (Cronbach’s α = 0.91). Descriptive statistics, independent samples t-tests, and Pearson correlation analysis were used to analyze the data.Results: The findings indicate that a significant negative correlation was found between perceived effectiveness and challenges (r = −0.312, p = .004), indicating a low-to-moderate negative correlation, where higher perceived effectiveness is associated with lower perceived challenges.Conclusion: Canva-based OCL supports collaborative project development while reducing barriers to digital collaboration. Nevertheless, challenges related to coordination, communication, and role distribution persist. The study extends OCL theory by positioning cloud-based design platforms as interactive learning environments that influence collaboration dynamics. Practically, the findings highlight the importance of structured instructional design, clear task allocation, and scaffolding strategies to maximize engagement and minimize collaboration barriers in project-based digital learning.